Analysis on the effect of the distances and inclination angles between human head and mobile phone on SAR. Issue 2 (November 2015) - Hossain, M.I.; Faruque, M.R.I.; Islam, M.T.
Abstract: The aim of this paper is to investigate the effects of the distances between the human head and internal cellular device antenna on the specific absorption rate (SAR). This paper also analyzes the effects of inclination angles between user head and mobile terminal antenna on SAR values. The effects of the metal-glass casing of mobile phone on the SAR values were observed in the vicinity of the human head model. Moreover, the return losses were investigated in all cases to mark antenna performance. This analysis was performed by adopting finite-difference time-domain (FDTD) method on Computer Simulation Technology (CST) Microwave Studio. The results indicate that by increasing the distance between the user head and antenna, SAR values are decreased. But the increase in inclination angle does not reduce SAR values in all cases. Additionally, this investigation provides some useful indication for future design of low SAR mobile terminal antenna.